The effects of bilingual instruction on the literacy skills of preschoolers - Aquino, Lalaine F. Yanilla (2005)
The effect of language of instruction on the acquisition of literacy skills in preschool children was investigated in this experimental study. Monolingual Filipino, monolingual English and bilingual instruction treatment had generally positive effects on the children's literacy skills in both Filipino and English. Monolingual instruction in either Filipino or English had a stronger effect on the children's literacy skills compared to bilingual instruction. Moreover, monolingual Filipino instruction, as compared to monolingual English instruction, apparently had stronger effect on the preschool children's literacy skills. Stronger effects were noted on the alphabet knowledge skills and phonological awareness skills and the weakest effects were on phoneme segmentation, decoding, and spelling in either language.
"April 2005."
Thesis (Ph.D. Education : Reading Education)--University of the Philippines, Diliman.
Best dissertation.
Keywords: Education, Bilingual -- Philippines; Language arts (Preschool) -- Philippines; Literacy -- Philippines; Preschool children -- Philippines